Representation and behavior - Keijzer, Fred A., 1960- (Bradford book., 2001)
Keijzer provides a reconstruction of cognitive science's implicit representational explanation of behavior, which he calls Agent Theory (AT), the use of mind as a subpersonal mechanism of behavior. Representation is a fundamental concept within cognitive science. Most often, representations are interpreted as mental representations, theoretical entities that are the bearers of meaning and the source of intentionality. This approach views representation as the internal reflection of external circumstances--that is, as the end station of sensory processes that translate the environmental state of affairs into a set of mental representations. Fred Keijzer stresses, however, that representations are also the starting point for a set of processes that lead back to the external environment. They are used as theoretical components within an explanation of a person's outwardly visible behavior. In this book Keijzer investigates the usefulness of representation for behavioral explanation, irrespective of mental issues. Viewing representation solely in terms of its contribution to explaining behavior allows him to build a serious case for a nonrepresentational approach and to evaluate representation's role in cognitive science. Keijzer provides a reconstruction of cognitive science's implicit representational explanation of behavior, which he calls Agent Theory (AT). AT is the use of mind as a subpersonal mechanism of behavior. He proposes an alternative to AT called Behavioral Systems Theory (BST), which explains behavior as the result of interactions between an organism and its environment. Keijzer compares BST to related work in the biology of cognition, in the building of animal-like robots, and in dynamical systems theory. Most important, he extends BST to the difficult issue of anticipatory behavior through an analogy between behavior and morphogenesis, the process by which a multicellular body develops.